Field notes contributed by Judith Carlson, fall 1987 - Carlson, Judithet al (1987)
Fall report of birds contributed by Judith Carlson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed